Reliability Analysis of a Distribution Network Using ETAP Software - Ebiarede, Perekebina; Unukoro, Patrick (My University, 2022)
The reliability of a distribution network is important to both electricity providers as well as consumers. This is even more so when the consumer consist of sensitive loads like hospital equipment as is the case with Delta State University Teaching Hospital (DELSUTH). Making use of data collected between February 2021 to January 2022 the reliability of the Delta State University Teaching Hospital (DELSUTH) 7.5 MVA, 33/11 kVA distribution network has been analyzed, on a sub-station by substation basis using the ETAP 16.0 software. Distribution system data as well as reliability data from DELSUTH has been used to model the network using ETAP 16.0 and to run reliability analysis on the network. Also analytical methods have been used to validate the ETAP 16.0 results for reliability based on interruption frequency and duration. Comparing the results obtained with the IEEE standard 1366 of 2011 it is seen that while most distribution substations of the DELSUTH network appear to meet up the IEEE standard in terms of interruption frequency (SAIFI) they however fall short of the standard in terms of duration of interruption (SAIDI)
Keywords: Reliability analysis; distribution network; reliability index; SAIFI; SAIDI; ETAP